Media Pembelajaran Berbasis Website pada Anak Usia Dini di Taman Kanak-Kanak Bintang Kecil - Sari, Nufia; Hasanah, Mahmudatun; Mayasari, Ovita (Politeknik Harapan Bangsa Surakarta, 2025)
All levels of education are required to adapt to current developments in the use of technology applied to classroom learning. This study was inspired by the growing need for accessible, interactive, and visually engaging educational tools. By integrating educational content with an easy-to-use interface and age-appropriate features. Through an interactive approach and oriented towards the developmental needs of early childhood, this website will be designed to provide an interesting and educational learning experience for preschool children who focus on playing while learning to recognize letters and numbers. The research method used is Rapid Application Development (RAD) to design and analyze web needs, chosen because the author believes this method is more flexible and efficient. The results show that web-based interactive learning can increase children's interest and involvement in the learning process, as well as provide practical guidance for teachers and parents in facilitating effective learning for preschool children through digital technology. The main conclusion from this research is that web-based interactive learning is an effective tool for supporting early childhood development. The application of technology to early childhood education can have a significant positive impact, especially in terms of children's engagement and motivation to learn. This research recommends the use of interactive websites as part of the early childhood education curriculum to improve the quality of learning.